Carrier dynamics and localization in AlInN/GaN heterostructures. Issue 5 (6th February 2013) - Marcinkevičius, Saulius; Liuolia, Vytautas; Billingsley, Daniel; Shatalov, Maxim; Yang, Jinwei; Gaska, Remis; Shur, Michael S.; Krishna, Sanjay; Plis, Elena
Abstract Photoexcited carrier dynamics and localization potentials in Al0.86In0.14N/GaN heterostructure have been examined by time‐resolved photoluminescence (PL), transient photoreflectance and scanning near‐field optical spectroscopy. The large GaN and AlInN PL intensity difference, and the short AlInN PL decay and GaN PL rise times indicate efficient photoexcited carrier transfer from AlInN to GaN via sub‐band edge states. Near‐field PL scans and photoreflectance data show that the diameter of the localization sites and the distance between them are well below 100 nm. Majority of these states is assigned to In clusters, in which the valence band has a higher energy than the valence band in a uniform AlInN alloy. It is likely that the carrier transport through the sub‐band edge states proceeds via high conductivity channels involving extended defects. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)